The effect of zinc to aluminium ratio and concentration of the anion on the formation of zinc-aluminium-4-chlorophenoxy acetate nanocomposite - Hussein, Mohd Zobir; Zainal, Zulkarnain; Yahaya, Asmah; Sarijo, Siti Halimah (Universiti Putra Malaysia Press, 2005)
Layered organic-inorganic hybrid nanocomposite material containing 4- chlorophenoxy acetate, (4-CPA) in an inorganic interlayer was prepared using 4-CPA as guest anion in Zn/Al layered double hydroxide inorganic host by direct coprecipitation method at various concentrations of 4-CPA between 0.1 and 1.6 M and Zn to Al molar ratios from 1 to 6. The pH of the solution was fixed at 7.5. PXRD diffractograms showed the formation of well-ordered nanolayered organic-inorganic hybrid nanocomposite for both cases, with the expansion of the basal spacing from 8.9 Å in the layered double hydroxide to 20.1-20.3 Å in the resulting nanocomposites. FTIR spectra for the nanocomposites (ZACs) indicated that the each spectrum composed of spectral features of Zn/Al-LDH (ZAL) and 4-CPA. This indicated that the 4-CPA was successfully intercalated into the ZAL interlayer. The N2 adsorption-desorption isotherms for both ZAL and ZAC synthesized at different 4-CPA concentrations showed that they are of Type IV, which indicated the mesoporous-type of material. Similar results were obtained for all the nanocomposites synthesized at different R values. The percentage of 4-CPA in the nanocomposites synthesized at different concentrations was 36-43 % (w/w) while the value of Zn to Al ratio (R) obtained from the elemental analysis was estimated to be 3.7-3.9 compared to the initial R value of 4 in the mother liquor. The values of R for the nanocomposites synthesized at different initial R values was very close to their respective initial values of the mother liquor while the percentage loading for 4-CPA for this nanocomposite was in the range of 38-44 % (w/w).